Mume clonal rootstocks for 'Aurora-1' peach in São Paulo State, Brazil - Newton Mayer, A.; Mendes Pereira, F. [UNESP] (My University, 2012)
In spite of significant results achieved with scion genetic improvement in stone fruits, the peach culture in Brazil still needs studies and new technologies regarding the use of rootstocks. A wide research project has being developed at the Faculdade de Ciências Agrárias e Veterinárias (FCAV/UNESP), Jaboticabal, Brazil, dealing with the use of mume clones (Prunus mume) as rootstocks for peach trees, which has produced promising results. In this research, two mume genotypes propagated by herbaceous cuttings were tested as rootstocks for peach cultivar Aurora-1. Three different tree spacing were used: 6 x 2 m, 6 x 3 m and 6 x 4 m. The experiment was carried out at Vista Alegre do Alto (21°10'14 S, 48°37'45 W, 700 m of altitude), São Paulo State, Brazil. Growing field conditions included Hapludalfs soil with medium sandy texture and using micro sprinkler irrigation. The region has an average chilling accumulation 17.9 hours per year. The evaluations were taken in 2005 and 2006 (2nd and 3rd year after planting, respectively). The trunk diameter was evaluated every three months, from the 24th to the 41st month after planting, totalizing seven evaluations. Plants on 'Rigitano' had higher trunk diameter on the 33rd, 39th and 41st month after planting (May/06, November/06 and February/07, respectively). No significant differences were observed in the other evaluations. The diameter at 5 cm above to the graft point was larger than below, but no incompatibility symptoms were observed between rootstocks and scion. Spacing tested did not influence trunk diameter, phenology and flower bud production in 'Aurora-1' scion. In conclusion, 'Rigitano' and 'Clone 15' are recommended for high density plantings of peach 'Aurora-1' in Brazil, and the 6 x 2 m spacing can be recommended, with productivity advantages for peach under low air relative humidity and mild winter conditions. © ISHS 2012.
Keywords: Flower bud; Low chill requirement; Phenology; Prunus mume; Prunus persica; Sprout bud; Trunk diameter; Prunus